PENGARUH PERINGKAT, KUPON, DAN SISA UMUR OBLIGASI TERHADAP YIELD TO MATURITY OBLIGASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Sipangkar, Helena; Silalahi, Donalson (LPPM Universitas Katolik Santo Thomas Medan, 2022)
This study aims to determine and explain the effect of the rating, coupon, and remaining life of bonds on the yield to maturity of bonds listed on the Indonesia Stock Exchange. To achieve this goal, a study was conducted on 17 bonds with a research period of 2017 – 2019 using purposive sampling as a sampling technique and multiple regression analysis as an analytical tool.The results showed that bond ratings had a negative and significant effect on yield to maturity, bond coupons had a positive and significant effect on yield to maturity, and the remaining life of bonds had a positive and significant effect on yield to maturity. The ability of these three variables to explain the variation in yield to maturity is 76.9 percent.